Maternal Parenting and Stunting Incidence in the Work Area of Tetaf Health Center - Nele, Maria M. R.; Boeky, Daniela L. A.; Nur, Marselinus Laga (Timorese Journal of Public Health, 2024)
Stunting is a problem of lack of nutritional intake in the long term resulting impaired growth and development in children. Inadequate feeding in maternal parenting is the cause of stunting problems. This study aims to determine the relationship between maternal parenting and the stunting incidence in the working area of ​​the Tetaf Public Health Center, South Central Timor District. The type of research was an analytic survey with a case control design. The research location was in the working area of ​​the Tetaf Public Health Center, South Central Timor Regency which was carried out in November-December 2022. The sample in this study was 64 respondents of mothers with toddlers who were divided into a control group of 32 respondents and a case group of 32 respondents. The analysis was univariate analysis and bivariate analysis with the chi-square test. The results of the research showed that there was a relationship between feeding practices (OR=18.455: 95%CL=4.575-74.439: p=0.000<0.05) and hygiene and sanitation (OR=7.222: 95%CL=2.309-22.588: p=0.001<0.05) with stunting. While the utilization of health services (p> 0.05) has no relationship with the incidence of stunting. Health workers are expected to be able to provide education to mothers under five to improve parenting by paying attention to feeding children related to nutritional according to the age group and the type of food the child needs, the child's personal hygiene, and the surrounding environment.